KAJIAN PENAMBAHAN SKIM DAN SANTAN TERHADAP KARAKTERISTIK YOGHURT DARI WHEY - ina siti nurminabari (Department of Food Technology, Universitas Pasundan, Bandung, 2018)
The purpose of this research was to obtain the the correlation ratio between the addition of skim milk and coconut milk on the characteristics yoghurt whey. The research method consists of two phases: a preliminary study and the main study. Preliminary studies done of the analysis of raw materials to the whey and coconut milk. The main research undertaken is to determine the correlation of the addition comparison of the characteristics skim milk yoghurt and whey. The design used is linear regression. The factor used is the ratio of the addition between skim and coconut milk (a) (a1 = 16: 6, a2 = 14: 8, a3 = 12: 10, a4 = 10: 12, a5 = 8: 14, and a6 = 6: 16). The response in the study include chemical response (analysis of lactic acid levels, pH, levels of protein, carbohydrates and fat), biological response (total cells) and organoleptic (color, viscosity, oddor, and taste). The results showed that the analysis of raw materials showed whey contains lactose component of 4.27%, amounting to 1.39% fat, and protein at 0.79%, while milk contains components for 32.007% fat and 1.56% protein. Comparison and skim milk used to provide correlation lactic acid content and pH of the yoghurt whey. Total number of cells in yoghurt whey in the range of 5,533,333 to 8,966,667 cells / ml. The addition comparison and skim milk does not affect the organoleptic testing the color and flavor but affect the viscosity and aroma. Selected product is on treatment a1 with a protein content of 5.808% and a fat content of 1, 089%.